A Comparative Study of Sensory Processing and Self-Care Skills in Children Aged 3–6 Years with Employed and Unemployed Mothers - Özgün Belen; Ezginur Gündoğmuş; Bilal Mert Bildiş; Gonca Bumin (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study aimed to compare sensory processing patterns and self-care skills of children aged 3-6 with employed and unemployed mothers. The main objective was to examine whether maternal employment status is associated with differences in sensory responsiveness and functional self-care performance during early childhood.Materials and Methods: A cross-sectional design was used. Twenty-six children with employed mothers and twenty-five children with unemployed mothers were included in the study. Sensory processing abilities were assessed using the Sensory Profile completed by caregivers. Self-care skills were evaluated by teachers using a standardised self-care assessment tool. Sociodemographic data were collected using a structured form Independent-samples t-tests and chi-square analyses were conducted to compare continuous and categorical variables.Results: Auditory processing scores were lower in children of employed mothers than in those of unemployed mothers (p = 0.002). Sensory threshold scores were higher in the employed-mother group (p = 0.013). Self-care scores did not differ significantly between the groups (p > 0.05). Categorical analyses revealed higher rates of atypical tactile processing (p = 0.034), emotional–social responses (p = 0.015), and sensory threshold classification (p = 0.029) in children with unemployed mothers.Conclusion: Maternal employment status may be associated with variations in children’s sensory processing patterns, whereas self-care skills appear more stable and routine-oriented. Environmental stimulation, social participation, and daily structure may contribute to these differences. Future research with larger samples and longitudinal designs is recommended.